Novel high-temperature supercapacitor combined dye sensitized solar cell from a sulfated β-cyclodextrin/PVP/MnCO3 composite1. Issue 19 (21st May 2015) - Selvam, S.; Balamuralitharan, B.; Karthick, S. N.; Savariraj, A. Dennyson; Hemalatha, K. V.; Kim, Soo-Kyoung; Kim, Hee-Je
<x xml:space="preserve">Abstract</x> A novel sulfated β-cyclodextrin/PVP/MnCO3 composite has been synthesized for a parallel-connected supercapacitor and dye-sensitized solar cell (counter electrode).